Optimization of Payroll Management through the Implementation of an Accounting System in the Public Sector - Minanda Putri Ramadhan; Tino Kemal Fattah; Putriana Salman (Journal of Business Transformation and Strategy, 2025)
Abstract: The Accounting Information System assists managers in making effective decisions. The payroll system is crucial for ensuring smooth operations in government institutions. A payroll system must include several documents used to determine an employee’s salary. This study employs a descriptive research approach. The research variable is the payroll accounting system of the Personnel and Human Resource Development Agency of Kotabaru Regency. The data used consists of primary and secondary data. Primary data includes payroll process data for flowchart processing, while secondary data comprises a brief history, organizational structure, and documents related to the payroll accounting system. Data collection methods involve interviews and documentation. The research findings indicate that the payroll accounting system for civil servants at the Personnel and Human Resource Development Agency of Kotabaru Regency has been implemented in accordance with accounting system standards